2015
DOI: 10.4103/0973-6247.162713
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platelet-rich plasma in treatment of androgenic alopecia

Abstract: Background:Platelet-rich plasma (PRP) has shown remarkable beneficial effects without any major adverse reactions in the treatment of androgenic alopecia. The growth factors in activated autologous PRP induce the proliferation of dermal papilla cells.Objectives:The objective was to investigate the clinical efficacy of PRP in treatment of androgenic alopecia.Materials and Methods:Ten patients were given autologous PRP injections on the affected area of alopecia over a period of 3 months at interval of 2-3 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 11 publications
2
81
1
4
Order By: Relevance
“…Various studies in the literature indicated that PRP stimulates a number of active features such as growth rate, hair count, hair density, hair shaft diameter, hair root strength, anagen hair, telogen hair, terminal hair density, epidermal keratinocytes, hair follicular bulge cells, and lead to increase in small blood vessels in hair follicle, prevents dermal papilla apoptosis, extent anagen phase, and enhances hair regrowth [70][71][72][73][74]. The carrier which contains dalteparin/protamine micro particles (DP MP) (low-molecular-weight heparin) was used to enhance the efficiency of PRP.…”
Section: The Mechanism Of Platelet-rich Plasma In Androgenetic Alopeciamentioning
confidence: 99%
“…Various studies in the literature indicated that PRP stimulates a number of active features such as growth rate, hair count, hair density, hair shaft diameter, hair root strength, anagen hair, telogen hair, terminal hair density, epidermal keratinocytes, hair follicular bulge cells, and lead to increase in small blood vessels in hair follicle, prevents dermal papilla apoptosis, extent anagen phase, and enhances hair regrowth [70][71][72][73][74]. The carrier which contains dalteparin/protamine micro particles (DP MP) (low-molecular-weight heparin) was used to enhance the efficiency of PRP.…”
Section: The Mechanism Of Platelet-rich Plasma In Androgenetic Alopeciamentioning
confidence: 99%
“…The positive effect of PRP in the treatment of AGA has been documented in other studies. [11,12,13].Mechanisms of hair regrowth induced by skin needling include: [14,15,16] release of platelet derived growth factor, epidermal growth factors through platelet activation and skin wound regeneration mechanism; activation of stem cells in the hair bulge area; overexpression of hair growth related genes vascular endothelial growth factor, B catenin, Wnt3a, and Wnt10 b. A 12-week study by Dhurat et al [17] showed that dermaroller along with Minoxidil treated group was statistically superior to Minoxidil treated group in promoting hair growth in men with AGA.…”
Section: Discussionmentioning
confidence: 99%
“…Son yıllarda gittikçe daha fazla uygulanan, diş hekimliğinden, dermokozmetolojiye ve kas iskelet sistemi hastalıklarına kadar geniş bir yalpezede uygulama alanı bulan PRP tedavisi her geçen gün üzerinde daha fazla çalışılan bir yöntem olarak dikkat çek-mektedir (7,8). Bizde kliniğimizde PRP tedavisi ile başarılı sonuç alınan kondromalazi patella tanılı olguyu vaka takdimi şeklinde tartışmayı amaçladık.…”
Section: öZunclassified